Penerapan Balanced Scorecard di Rumah Sakit Indonesia: Systematic Review - Avenia Dionisia Menna; Nauri Anggita Temesvari (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2022)
A systematic review is a research method that summarizes primary research results to present facts that are more comprehensive and balanced. A balanced scorecard is a concept for measuring the performance of an organization with 4 (four) different perspectives, namely customer perspective, financial perspective, internal business perspective, and learning and growth perspective. The results of the initial article screening using the database literature on google scholar obtained 513 journals, science direct obtained 7 journals and GARUDA obtained 20 journals with the keywords